1994
DOI: 10.1111/j.1439-0396.1994.tb00338.x
|View full text |Cite
|
Sign up to set email alerts
|

Ergosterin und Fusarientoxine in Weizenkleie und Weizen

Abstract: Zusammenfassung Proben von Weizenkleie und Weizen aus Chargen, die hauptsächlich für Fütterungszwecke bestimmt waren, wurden in zwei Jahren in einem Gebiet Südwestdeutschlands gezogen und auf Ergosterin (ERG), einen Parameter für die von Pilzen gebildete Biomasse, sowie auf die Fusarientoxine Deoxynivalenol (DON) und Zearalenon (ZEA) untersucht. ERG, DON bzw. ZEA wurden in 100, 100 bzw. 71% der Kleieproben, und in 100, 74 bzw. 18% der Weizenproben gefunden. Der mittlere Gehalt von ERG, DON bzw. ZEA lag bei 11,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1996
1996
2008
2008

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…Low ERG concentrations were recorded in flours with a high degree of purification, while higher levels were found in flours of lower milling grades. When comparing the results reported in this study with literature data we may state that, e.g., for wheat flour Müller & Schwadorf (1993) found concentrations ranging from 4.0 to 35.8 mg/kg, while Müller et al (1994) reported 11.7 mg/kg; for corn flour Maupetit et al (1993) reported the levels from 3.0 to 5.0 mg/kg. On the basis of the above results it may be suggested that ERG concentration in the presented investigations was lower than in the studies cited above.…”
Section: Resultsmentioning
confidence: 60%
“…Low ERG concentrations were recorded in flours with a high degree of purification, while higher levels were found in flours of lower milling grades. When comparing the results reported in this study with literature data we may state that, e.g., for wheat flour Müller & Schwadorf (1993) found concentrations ranging from 4.0 to 35.8 mg/kg, while Müller et al (1994) reported 11.7 mg/kg; for corn flour Maupetit et al (1993) reported the levels from 3.0 to 5.0 mg/kg. On the basis of the above results it may be suggested that ERG concentration in the presented investigations was lower than in the studies cited above.…”
Section: Resultsmentioning
confidence: 60%
“…These observations upon effects of storage on chemical composition of the pelleted concentrates are in line with fi ndings on the hygienic quality of the pellets. Signifi cant modifi cations of chemical composition during storage would have indicated enhanced microbial activity and growth, paralleled by an increase in microbial and, particularly fungal, biomass for which ergosterol has been used as a chemical marker in cereal grains and grain by-products (Müller and Lehn, 1988;Müller et al, 1994) and compound feeds (Bailly et al, 1999). The vast majority of ergosterol concentration was considerably lower than 'preliminary normal ranges' for these types of feeds (6.1 to 6.6 mg/kg; calculated according to Schwadorf, 1988, 1990), therefore indicating products of excellent hygienic quality.…”
Section: Discussionmentioning
confidence: 99%